An Evaluation of Some Marking Techniques Used on Bobwhite Quail - David Urban; W. D. Klimstra (National Quail Symposium Proceedings, 2017)
Summarized are data obtained from field testing various marking techniques used to distinguish individual, unrestrained bobwhite quail. Four methods and combinations of each included various types of back tags, colored leg bands, dyes, and radio transmitters. Discussed are methods, advantages, and limitations as based upon field observations of 195 back-tagged quail, 86 quail with colored leg bands, 55 dyed quail, and 91 radio-marked quail.